Pro-neuronal activity of Myod1 due to promiscuous binding to neuronal genes - Lee, Qian Yi; Mall, Moritz; Chanda, Soham; Zhou, Bo; Sharma, Kylesh S.; Schaukowitch, Katie; Adrián Segarra, Juan Manuel; Grieder, Sarah D.; Kareta, Michael S.; Wapinski, Orly L.; Ang, Cheen Euong; Li, Rui; et al. (Nature cell biology, 2020)
Lee, Mall et al. explore why the sequence-related transcription factors Myod1 and Ascl1 lead to different reprogramming outcomes when expressed in fibroblasts, despite binding similar targets.